Space in Language and Linguistics: Geographical, Interactional, and Cognitive Perspectives - Auer, Peter; Hilpert, Martin; Stukenbrock, Anja; Szmrecsanyi, Benedikt (De Gruyter, 2013)
Space; Geolinguistics; Interaction; Cognition